Competitive Advantage and Firm Performance: Debt Financing as a Moderating Variable - Rita, Maria Rio; Hidayat, Riskin; Kristanto, Ari Budi (JDM (Jurnal Dinamika Manajemen), 2022)
This study aims to examine the moderating role of debt financing in the effect of competitive ad- vantage on the performance of Lasem-Rembang batik MSMEs. Capital from debt is expected to optimize the role of competitive advantage to strengthen firm performance. The researchers used primary data through a survey of 68 batik MSME entrepreneurs who have been operating for at least 5 years. The data was processed using Partial Least Squares-Structural Equation Model (PLS)-SEM with the WarpPLS 7.0 application by including the control variable of entrepreneur education level. The findings show that competitive advantage is not proven to have a positive effect on the perfor- mance of MSMEs; on the contrary, it has a significant negative effect. Then debt financing is demon- strated to moderate the effect of competitive advantage on MSME performance. This implies that debt financing can strengthen the effect of competitive advantage on MSME performance because it produces a positive and significant effect.